Investigations of the effective temperature of sheared colloids and dynamic behavior of glass-forming liquids - Zhang, Min, author; Szamel, Grzegorz, advisor; Ladanyi, Branka, committee member; Bernstein, Elliot, committee member; Chen, Eugene, committee member; Bradley, R. Mark, committee member (Colorado State University. Libraries, 2013)
There are three projects in my dissertation. In chapter 2, a simple colloidal suspension under shear is studied. Four different methods are used to define the so-called effective temperature. The effective temperature calculated from the extended fluctuation-dissipation theorem is independent of the choice of the observables, and it controls the density distribution profiles. All the effective temperatures are larger than the bath temperatures. The effective temperature along the velocity gradient direction is somewhat larger than that along the vorticity direction. In chapter 3, a binary Lennard-Jones mixture at different temperatures is investigated. Due to the presence of shear flow, the ergodicity is recovered when the temperature is below glass transition. The dynamic behavior of the system is investigated. Above the glass transition, the dynamics is primarily controlled by the temperature, while below the glass transition, shear flow plays a dominant role. The violation of the Stokes Einstein relation, as well as the exponential tails in the self-part of the van Hove function are observed. In chapter 4, a binary hard-sphere mixture is researched. Four-point correlation functions are calculated, which suggest the presence of dynamic heterogeneity. To calculate four-point correlation functions, we need to specify the 'measuring stick' (the parameter a in the overlap function Fo(a, t)). When a is large enough, the four-point susceptibility at the structural relaxation time is independent of the choice of a. The dynamic correlation length is estimated from the Ornstein-Zernike fits for the four-point structure factor. We speculate that the maximum value of the dynamic correlation length is also independent of the 'measuring stick'.
Keywords: dynamic heterogeneity; sheared colloids; glass transition; effective temperature; four-point correlation functions; computer simulation